From allies to partners: a historical analysis of UK-US Relations - Muhamad Zaki Abd Aziz; Norhidayu Rosli (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article examines the historical trajectory of the United Kingdom-United States relationship, tracing its evolution from the early 20th century to the present. The study aims to explore how this "special relationship" has developed over time, shaped by geopolitical events, shared values, and mutual strategic interests. While widely recognised as a key partnership, challenges such as diverging priorities and shifting global dynamics have periodically tested its resilience, necessitating a deeper exploration of its historical foundations. Employing a qualitative methodology, the research utilises historical analysis of primary and secondary sources, including diplomatic correspondence, treaties, and academic literature. A thematic approach is adopted to investigate critical phases of the relationship, such as World War II, the Cold War, and the post-Cold War era. Findings reveal that the UK-US relationship has oscillated between periods of profound cooperation and moments of divergence, driven by factors such as economic interdependence, military alliances, and shared democratic principles. Despite these challenges, the relationship's adaptability and resilience have solidified its role as a cornerstone of Western geopolitics. This study enhances the understanding of transatlantic relations by offering insights into the historical dynamics that continue to influence contemporary global affairs. It underscores the UK-US partnership as a model of strategic collaboration and provides lessons for nurturing enduring alliances in an increasingly multipolar world.